The Influence of Service Quality and Perceive Quality and its’ effect towards BPJS Outpatients Satisfaction; A Study at Bayu Asih Hospital, West Java - Frianto, Dedy; Aliyani Mardiana, Lina; Reoespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
Based on (PerMenKes) Rule No. 43 of 2016 about Minimum Standards of Services in the Field of Health stated that the government has the responsibility to ensure that every citizen receives quality health services. This is regulated in the Minimum Service Standards in the health sector. Implementation of Minimum Service Standards will be very strategic in relation to implementation of Health Insurance: Jaminan Kesehatan Nasional (JKN). Implementation of minimum service Standard will strengthen the promotive-preventive side so that it is expected to have an impact on reducing the number of curative cases that must be covered by JKN. Government and private hospitals are one of the health facilities that visited by many people in obtaining the right to health services. The development of a dynamic community mindset requires hospitals to always make adjustments to improve quality and conduct direct surveys in order to find out factually the needs of consumers. Therefore, hospitals are required to provide quality services in accordance with established standards and can required all levels of society. Hospital has a standard minimum of service in every kind of service, indicator and standard can be seen in the table 1.